POTENTIAL HUMAN SEWAGE INTO RENEWABLE ENERGY AND ORGANIC FERTILIZER PLANTS IN SOCIETY - Simbolon, Lambok Parulian (MATTER: International Journal of Science and Technology, 2015)
Human excrement or feces is considered extremely disgusting by the man himself, even rarely used as organic fertilizer. Stool very useful in mixing ingredients in organic fertilizer or planting medium. On the other hand, the stool has a great potential to be used as biogas, as well as cow dung the is now used as a biogas flare. With the human population is very much, the stool has a very high probability to be used in biogas. Furthermore, waste biogas can be used as organic fertilizer for crops.